Punching Shear Resistance of Slab with Shear Reinforcement According to Armenian and Foreign Building Standards - Hovhannes Avagyan (Tehnički Vjesnik, 2019)
The paper presents the results of punching shear values with reinforcement based on calculations of two and four storey cast-in-place reinforced concrete flat plate system buildings with spans of 4 m and 7 m by LIRA, Design Expert and RCM ACI-builder software in accordance with Armenian, Russian, European and American building standards under earthquake loading. In contrast to Eurocode 2 (EN 2) and American Concrete Institute (ACI), the building codes of the Republic of Armenia (SNiP) do not include the influence of bending moment in shear stress equation. The effect of punching shear on both interior and edge columns was carried out. To analyze the systems finite element method (FEM) was used. The results of comparison analysis show that according to SNiP the shear stresses do not exceed the limit even without reinforcement, whereas by foreign standards the differences between peak shear stresses with reinforcement and permissible shear reinforcement are marginal.